Managing a two-echelon supply chain with price, warranty and quality dependent demand - Nikunja Mohan Modak; Shibaji Panda; Shib Sankar Sana (Cogent Business & Management, 2015)
This paper deals with a two-layer supply chain composed of one manufacturer and one retailer for single-type product. The demand function of the end customers depends on quality, warranty, and sales price of the product. The profit functions of the manufacturer and the retailers are maximized under centralized and decentralized approaches. Our study suggests that the joint profit in centralized system is always more than the decentralized system. Finally, the surplus profit in centralized system is shared according to their profits in decentralized system.